State and religious diversity: reflections on post‐1947 India - SINGH, GURHARPAL (Totalitarian movements and political religions, 2004)
This article critically reviews the assumptions underlying state secularism in India since 1947 against the policies of different regimes in managing religious diversity. It reflects on how the construction of secularism was adapted to Indian conditions in ways which enabled it to coalesce with existing traditions of statecraft and the religious ideals of Mohandas K. Gandhi, on the one hand, and the modernist outlook of Jawaharlal Nehru, on the other. This fine balance, it is suggested, was seriously compromised by post‐1947 Congress governments. Since the 1980s state secularism has also been under attack by the political forces mobilised by Hindutva and ‘anti‐secularists’ who draw their inspiration from neo‐Gandhism and post‐colonial theory. Despite the critiques offered by these two schools of thought, a general assessment of the post‐1947 experience, this article argues, suggests that Nehru’s ideals offer the most promising prospectus of building democracy in a religiously diverse society such as India. More broadly the Indian experience offers interesting lessons about the current debate on the place of organised religions in public life.